Health Management Training of UGs- A Missed Opportunity! - Sunder Lal; Bishwaraj Inglageri (Indian Association of Preventive and Social Medicine, 2020)
The objectives of UGs medical education have been clearly defined. At the end of undergraduate program, the Indian Medical graduate should be able to recognize " Health for All" as a national goal, learn every aspect of national policies on health, achieve competency in holistic medicine, develop scientific temper and observe medical ethics. In consonance with the national goals, each medical institution should evolve institutional goals to define the kind of trained manpower they intend to produce. The indian medical graduates coming out of medical colleges be familiar with the basic factors which are essential for the implementation of national health programs, acquire basic management skills in the area of human resources, material and resource management related to health care delivery system, general and hospital management, principal inventory skills and counselling.